(untitled) (Research, Society and Development, 2020)
In this research we contextualize the interdisciplinarity concept in the evolution of its practice at the Federal University of ABC (UFABC), during the ten first years of its constitution. The work is the result of a case study with a qualitative approach that analyzed the pedagogical project of constitution of the Bachelor of Science and Technology (BC&T) of UFABC and proposed a discussion based on the main authors who approached the subject with the view of some of the main teachers involved in this trajectory. The discussions had as a starting point the observation of a class, which took place during a course of the UFABC Postgraduate Program in Humanities and Social Sciences, in the third quarter of 2016. We found that in the trajectory of interdisciplinarity at UFABC, curriculum flexibility was maintained for the new pedagogical proposals that were being built, however, according to the analysis of the documents and discussions on the topic, we verified that there are signs of a distance between its idealization and the realization of interdisciplinary proposals, showing an approximation of multidisciplinary practices of the implemented actions.